On The Electricity Demand In Relation To Rise Of Electric Vehicles In Malaysia - Yeap, Yi Ling (Universiti Sains Malaysia, 2018)
The demand for electric vehicles is increasing rapidly in advanced countries due to various factors. With increasing number of fully electric or plug-in hybrid vehicles, a study is done on the demand for electricity in relation to rise of electric vehicles. The strategic green technology implementation to overcome potential challenges in Malaysia is also identified. A quantitative of correlation method is used to research the key factors affecting the number of electric vehicles against the electricity demand in Malaysia. This research mainly is to indicate the relationship between the factors affecting number of electric vehicles and electricity demand. The trend of the global market for electric vehicles is studied and a regression method is used to determine the future projection modelling of electric vehicles. The successful implementation of electric vehicles will also require strategic directions that are practicable and achievable. This research identifies strategic thrusts, in line with the National Green Technology Policy where Government's intervention is essential to drive changes in order to create conducive ecosystems for the development of electric vehicles (EV). This research recognises the strengths and weaknesses in the existing system, and provides action points for the relevant Government entities and/or private sector to act on. This research is essential for Malaysia to be prepared to face the phenomenon that could take our nation by storm. The strategic directions to overcome challenges that are considered in this research encompass several aspects which will need to work in tandem.